2020
DOI: 10.1186/s12864-020-06877-4
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive duplication, biased molecular evolution and comprehensive functional analysis of the PP2C family in Glycine max

Abstract: Background: Soybean (Glycine max) is an important oil provider and ecosystem participant. The protein phosphatase 2C (PP2C) plays important roles in key biological processes. Molecular evolution and functional analysis of the PP2C family in soybean are yet to be reported. Results: The present study identified 134 GmPP2Cs with 10 subfamilies in soybean. Duplication events were prominent in the GmPP2C family, and all duplicated gene pairs were involved in the segmental duplication events. The legume-common dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…2, 5B), indicating the functional similarity and specificity of these JrPP2C genes. Moreover, the gene and protein structural features of JrPP2Cs were similar to those of PP2C in Glycine max [44], Gossypium hirsutum [45], Brassica rapa [46] and Brachypodium distachyon [47]. Soybean PP2Cs could control plant growth and development [44].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…2, 5B), indicating the functional similarity and specificity of these JrPP2C genes. Moreover, the gene and protein structural features of JrPP2Cs were similar to those of PP2C in Glycine max [44], Gossypium hirsutum [45], Brassica rapa [46] and Brachypodium distachyon [47]. Soybean PP2Cs could control plant growth and development [44].…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the gene and protein structural features of JrPP2Cs were similar to those of PP2C in Glycine max [44], Gossypium hirsutum [45], Brassica rapa [46] and Brachypodium distachyon [47]. Soybean PP2Cs could control plant growth and development [44]. Cotton PP2C gene family plays critical role in organ and fiber development, as well as abiotic stress tolerance [45].…”
Section: Discussionmentioning
confidence: 93%
“…Compared to previous studies [ 28 ], the latest version of GFF3 annotation file was used to determine PP2C and SnRK2 genes of Williams 82, which would be more accurate to reveal the structure and function of the two gene families. In addition, Zhang et al and Fan et al both only observed expression patterns of these genes at different tissues, and neither elaborated the mechanic networks under drought stress related to the ABA signaling pathway [ 29 , 34 ]. In this study, we focus on the abundance of PP2C-A and SnRK2 members under ABA and drought treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved motifs of the KUP family in G. hirsutum, G. barbadense, G. arboretum, and G. raimondii were identified with MEME (http://meme-suite.org/tools/meme) (Bailey et al, 2009). Parameters were set on the basis of values that were previously used to analyze putative motifs (Fan et al, 2019;Fan et al, 2020). The identified motifs were further annotated by using CDD (Marchler-Bauer et al, 2015).…”
Section: Structural and Promoter Analysismentioning
confidence: 99%